2013
DOI: 10.1007/s00415-013-7140-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes and associated factors of clopidogrel resistance in patients after cerebral infarction

Abstract: Stroke victims often exhibit clopidogrel resistance (CR). This prospective study was undertaken to observe changes that influence CR in the secondary prevention of cerebral infarction (CI). The study included 56 cases at high risk of stroke (HRS), 147 cases of CI and 68 control subjects. The CI and HRS groups were divided into CR and NCR (none clopidogrel resistance) subgroups using standard criteria. The NCR group was subdivided into DCR (dynamic CR) and CNCR (continuous NCR) groups. Platelet aggregation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In our study, we observed similar association in patients with coronary artery disease. High total cholesterol levels were also associated with HTPR in patients with cerebral infarct undergoing clopidogrel treatment ( 40 ). Moreover, we observed the same association in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed similar association in patients with coronary artery disease. High total cholesterol levels were also associated with HTPR in patients with cerebral infarct undergoing clopidogrel treatment ( 40 ). Moreover, we observed the same association in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic complications after treatment occurred in two patients. Previous reports indicated that levels of P2Y12, a platelet membrane protein receptor which plays a key role in platelet activation, vary in individuals and influence the effect of antiplatelet therapy 26 27. To reduce ischemic complications for these patients receiving reconstructive endovascular treatment, P2Y12 platelet function tests, to evaluate if there is P2Y12 resistance to antiplatelet therapy, and coagulogram tests, such as thrombelastography to monitor blood coagulation, may be helpful 27.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a lower responsiveness to Clopidogrel therapy in our stroke population is consistent with a wide variety of previous studies. 19,27,44 The phenomenon named "Clopidogrel resistance," highly variable in different populations (ranging from 15.9% to 49.5%), 45 has been widely reported in association with worse clinical outcomes in patients with cardiovascular events. The cause of this phenomenon is known to be multifactorial because it seems to be dependent on several issues: choice of assay and cutoff value, 6 timing of testing, pharmacokinetic, drugdrug interactions, comorbidities, age, genetic polymorphisms, and poor compliance.…”
Section: Article In Pressmentioning
confidence: 99%